2006
DOI: 10.2215/cjn.00030505
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Relation among Depression Symptoms, Cardiovascular Disease Events, and Mortality in End-Stage Renal Disease

Abstract: Temporal relationships among depression, medical comorbidity, and death or cardiovascular disease (CVD) events are complex. Clarifying temporal relationships may enhance current insight regarding the nature of the association of depression with poor outcomes. The temporal relation of depression symptoms (DS; score <52 on five-item Mental Health Index) assessed at 6-mo intervals for 2 yr to CVD event, all-cause death, cardiovascular disease deaths, and non-cardiovascular disease deaths was studied in 917 incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
182
6
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 169 publications
(197 citation statements)
references
References 57 publications
8
182
6
1
Order By: Relevance
“…Our findings extend the findings in the work by Boulware et al (11), which showed that MHI scores used for screening for depressive affect predict survival and CVD deaths in incident HD patients when assessed in a time-varying analysis but not when assessed only at baseline. The work by Kimmel et al (30) showed the importance of following the course of depressive affect, because there was no significant association between baseline depressive affect and mortality in prevalent dialysis patients.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our findings extend the findings in the work by Boulware et al (11), which showed that MHI scores used for screening for depressive affect predict survival and CVD deaths in incident HD patients when assessed in a time-varying analysis but not when assessed only at baseline. The work by Kimmel et al (30) showed the importance of following the course of depressive affect, because there was no significant association between baseline depressive affect and mortality in prevalent dialysis patients.…”
Section: Discussionsupporting
confidence: 89%
“…It was interesting to note that, despite the numerous biases in using the time-varying Cox model, we found approximately the same trends of results in time-varying Cox regression analysis (data not shown). We also got the same trends of results when we analyzed with cutoff of 52, which was used in another study (11).…”
Section: Sensitivity Analysissupporting
confidence: 54%
See 3 more Smart Citations